2022
DOI: 10.1073/pnas.2209852119
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic analysis of cell-free DNA by fragmentomic profiling

Abstract: Cell-free DNA (cfDNA) fragmentation patterns contain important molecular information linked to tissues of origin. We explored the possibility of using fragmentation patterns to predict cytosine-phosphate-guanine (CpG) methylation of cfDNA, obviating the use of bisulfite treatment and associated risks of DNA degradation. This study investigated the cfDNA cleavage profile surrounding a CpG (i.e., within an 11-nucleotide [nt] window) to analyze cfDNA methylation. The cfDNA cleavage proportion across positions wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…Still, motif diversity score (MDS), an aggregate measure of motif distribution through normalized Shannon entropy, was not significantly different between clinical states ( Figure 4b-c ). Recently, Zhou et al 30 demonstrated that cfDNA fragment cleavage patterns could be quantified by non-negative matrix factorization of 4-mer end motifs into “founder” end motif profiles (F-profiles). We found that indeed, motifs contributed non-randomly to F-profiles ( Supplemental Figure 1 ), F-profile contributions to cfDNA samples differed between clinical states ( Figure 4d ), and that specific F-profiles were more accurate than individual motifs in differentiating clinical states.…”
Section: Resultsmentioning
confidence: 99%
“…Still, motif diversity score (MDS), an aggregate measure of motif distribution through normalized Shannon entropy, was not significantly different between clinical states ( Figure 4b-c ). Recently, Zhou et al 30 demonstrated that cfDNA fragment cleavage patterns could be quantified by non-negative matrix factorization of 4-mer end motifs into “founder” end motif profiles (F-profiles). We found that indeed, motifs contributed non-randomly to F-profiles ( Supplemental Figure 1 ), F-profile contributions to cfDNA samples differed between clinical states ( Figure 4d ), and that specific F-profiles were more accurate than individual motifs in differentiating clinical states.…”
Section: Resultsmentioning
confidence: 99%
“…Of course, other models integrating other descriptors, eg, epigenetic marks [36] or fragment sizes [17], other loci and based on a more diverse set of data must be designed to provide a tool usable at the bedside. We hope that our findings, in particular, those with regards to the use of noncoding RNAs, will help improve the sensitivity of ctDNA detection and help widespread liquid biopsy applications.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In cancer cells, they participate in structural changes, probably through homologous recombination given their widespread distribution throughout the genome and highly similar sequences (2). Moreover, Alu elements are hypomethylated early during tumor progression (3)(4)(5)(6)(7)(8)(9), and this feature has been incorporated into methods for the earlier detection of cancer through plasma cell-free DNA (cfDNA) analysis (10). Alu elements also reflect the altered fragmentation patterns found in the cfDNA of patients with cancer: One of the first plasma multicancer biomarkers used quantitative polymerase chain reaction (qPCR) to calculate the ratio of short and long Alu segments (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%